Catalytic activity of sulfuric acid on the morphology of electrochemically obtained copper powder - Miomir G. Pavlović; Nebojša D. Nikolić; Goran Bošković (Zaštita Materijala)
The subject of the research is influence of sulfuric acid on morphology of electrochemically obtained copper powder during galvanostatic electrolysis mode. In this paper electrodeposition of copper powder from sulphate electrolyte was carried out. Electrolytes with three different concentrations of Cu2+ (7 g/dm3, 18 g/dm3 and 33 g/dm3) were used, each in combination with three different concentrations of H2SO4 (100 g/dm3, 150 g/dm3 and 200 g/dm3), so that copper powder was deposited from nine electrolytes. Copper wire with surface area of 1cm2 was used as cathode, and copper anode in the form of metal sheet was pressed against the wall of electrochemical cell that had volume of 500 cm³. Experiments were carried out at room temperature, and electrolyte stirring was performed using a magnetic stirrer. Copper powder was deposited galvanostatically at current densities of j = 1500 A/m2, j=2000 A/m2 and j=2500 A/m2. Produced copper powder was removed from cathode every three minutes. All the characteristics of powder depend on the size and shape (morphology) of particles and they are mutually correlated. Research of morphology and size of particle was carried out using scanning electron microscopy (SEM). Increase of H2SO4 concentration causes increase in branching of copper powder. It was concluded that the size of copper powder grains reduces with the increase in concentration of H2SO4.